Combined maternal risk factors and the Quadruple test to predict late-onset preeclampsia in pregnant Thai women - Phattarika Bunyapipat; Ninlapa Pruksanusak; Chitkasaem Suwanrath; Alan Geater (BMC Pregnancy and Childbirth, 2023)
Abstract Background This study aimed to evaluate the predictive power of a model combining maternal risk factors and the Quadruple screen test for late-onset preeclampsia (PE). Methods All pregnant women that received the Quadruple test for Down syndrome at 15+ 0-20+ 6 weeks’ gestation were recruited. Maternal serum α-fetoprotein, β-human chorionic gonadotropin, unconjugated estriol, and inhibin A were measured as multiples of the median. A logistic regression model was used to identify predictors associated with late-onset PE with severe features. The receiver operating characteristic (ROC) curve and area under the curve (AUC) were used to assess the model’s predictive ability. Results Fifty-five of the 2,000 pregnant women had PE, and 31 of 55 women had late-onset PE. Multivariate analysis identified maternal age ≥ 35 years, inhibin A, history of previous PE, history of infertile, cardiac disease, chronic hypertension, and thyroid disease as significant risk factors. The area under the curve of the receiver operating characteristic curve was 0.78. The likelihood ratio to predict late-onset PE was 49.4 (total score > 60). Conclusions Our model combining serum inhibin A with maternal risk factors was useful in predicting late-onset PE. Close monitoring of these patients is recommended.